A simple biochemical plasma test as an indicator of maternal energy balance predicts offspring survival in bighorn sheep - Laliberte, Connor; Devan-Song, Anne; Burco, Julia D.; Couch, Claire E.; Gentzkow, Morgan F.; Spaan, Robert S.; Epps, Clinton W.; Beechler, Brianna R. (Frontiers in Ecology and Evolution, 2023)
In species where offspring survival is highly variable relative to adult survival, such as bighorn sheep (Ovis canadensis), physiological indicators of maternal investment could clarify the functional mechanisms of life history trade-offs and serve as important predictors of population dynamics. From a management perspective, simple predictors of juvenile survival measured non-lethally from maternal samples could aid in identifying at-risk populations or individuals before significant mortality occurs. Blood biochemical parameters can offer low-cost insights into animal health and physiology, therefore we sought to develop a simple biochemical predictor of juvenile survival based on maternal blood samples. We measured biochemical indicators of energy balance in adult bighorn sheep at a single time point in January or February, and then monitored survival through August of the same year to assess how those measures related to survival of individual adults and their juvenile offspring. Juvenile survival was lower over the subsequent spring and summer when maternal adult serum beta-hydroxybutyric acid (β-HBA) concentration was high, indicating a negative energy balance in the mothers. However, serum β-HBA did not correlate with adult survival over the same period. Our findings suggest that even when maternal body condition is high, short-term caloric deficit may be sufficient trigger to decrease investment in offspring survival. This mechanism could protect adult females from investing heavily in juvenile survival when resources become too limited to support population growth. Our study suggests that β-HBA could be a powerful monitoring tool for bighorn sheep and other threatened ruminant populations under resource limitation.